The quest for successful Atlantic salmon restoration: perspectives, priorities, and maxims - Lennox, Robert J; Alexandre, Carlos M; Almeida, Pedro R; Bailey, Kevin M; Barlaup, Bjørn T; Bøe, Kristin; Breukelaar, André; Erkinaro, Jaakko; Forseth, Torbjørn; Gabrielsen, Sven-Erik; Halfyard, Edmund; Hanssen, Erlend M; et al.
2021